Animal hide and seek: usborne touchy feely farmyard tales - Cartwright, Stephen (Usborne China, 2018)
Join Poppy and Sam as they play hide-and-seek on Apple Tree farm! With flaps to lift and lots of furry and textured patches to explore, this book introduces the popular characters from Apple Tree Farm to very young children. A delightful book for adults and children to share.